PERFORMA FUNGSIONAL DAN KINEMATIKA EKSTREMITAS BAWAH ATLET REMAJA DENGAN CHRONIC ANKLE INSTABILITY: STUDI MATCHED-CONTROL - Dimas sondang irawan; Anita Faradilla Rahim; Erwanico Syahputra; Arif Abdullah (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2026)
Chronic Ankle Instability (CAI) impairs neuromuscular control and dynamic stability in adolescent athletes, with growing evidence of associated kinematic alterations in the lower extremity. To compare functional performance and lower extremity kinematics between adolescent athletes with and without CAI. A matched-control cross-sectional study involving 60 adolescent athletes aged 16–17 years (30 CAI, 30 controls), matched by age, sex, sport type, and limb dominance. Functional performance was assessed using the Functional Reach Test (FRT), Agility T-Test, 20-metre Sprint, Side Hop Test, and CAST. Lower extremity kinematics (knee valgus, dorsiflexion, hip flexion) were assessed via 2D video analysis using Kinovea software (60 Hz camera) during functional tasks. CAIT was used for group classification (CAI: ?24; control: ?28). Independent t-test was used (p < 0.05). The CAI group demonstrated significantly longer Side Hop Test time (3.43 ± 0.19 s vs. 2.94 ± 0.15 s; p < 0.001; d = 2.88), greater knee valgus (14.43 ± 2.56° vs. 8.92 ± 1.60°; p < 0.001; d = 2.58), reduced dorsiflexion (27.84 ± 3.99° vs. 35.67 ± 2.61°; p < 0.001; d = 2.32), and reduced hip flexion (41.43 ± 3.59° vs. 48.05 ± 2.09°; p < 0.001; d = 2.26). No significant differences were found in FRT, T-Test, Sprint, or CAST. CAI in adolescent athletes is associated with clinically meaningful deficits in reactive lateral hopping and multi-segmental kinematic alterations. Integration of Side Hop Test and 2D kinematic screening is recommended for functional assessment of this population.